2013
DOI: 10.1002/ece3.719
|View full text |Cite
|
Sign up to set email alerts
|

Identification of molecular and physiological responses to chronic environmental challenge in an invasive species: the Pacific oyster, Crassostrea gigas

Abstract: Understanding the environmental responses of an invasive species is critical in predicting how ecosystem composition may be transformed in the future, especially under climate change. In this study, Crassostrea gigas, a species well adapted to the highly variable intertidal environment, was exposed to the chronic environmental challenges of temperature (19 and 24°C) and pH (ambient seawater and a reduction of 0.4 pH units) in an extended 3-month laboratory-based study. Physiological parameters were measured (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
53
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 73 publications
11
53
2
Order By: Relevance
“…The echinoderms and shelled molluscs are vulnerable to seawater acidification and warming because their calcified tissues are formed from highly soluble crystals (Dupont et al, 2010). Consistent with the result for Pacific oyster C. gigas (Clark et al, 2013), elevated temperature enhanced the effect of seawater acidification on NCR in M. edulis. In addition to NCR, elevated temperature also enhanced the reduction in Ca/Mg ratio caused by seawater acidification.…”
Section: Discussionsupporting
confidence: 65%
“…The echinoderms and shelled molluscs are vulnerable to seawater acidification and warming because their calcified tissues are formed from highly soluble crystals (Dupont et al, 2010). Consistent with the result for Pacific oyster C. gigas (Clark et al, 2013), elevated temperature enhanced the effect of seawater acidification on NCR in M. edulis. In addition to NCR, elevated temperature also enhanced the reduction in Ca/Mg ratio caused by seawater acidification.…”
Section: Discussionsupporting
confidence: 65%
“…HSP70 genes have previously shown strong correlation with chemical exposure, including hydrocarbons as used in this study, and have been suggested as candidate biomarkers for environmental toxicology (Boutet et al, 2004;Cruz-Rodríguez and Chu, 2002;Snyder et al, 2001). In these studies the inducible form of HSP70 was targeted in a candidate gene approach, as these were the only gene data available at the time, but more recent analyses have shown HSP70-12B to be induced in response to thermal challenge in C. gigas (Clark et al, 2013). Table 4 should be placed here…”
Section: Transcripts Encoding Putative 70kda Heat Shock Proteins (Hsp70)mentioning
confidence: 99%
“…The latter method may prove particularly useful where there is an expansion in gene family members and it is not necessarily the "classical", best known family members that are responsive to the chemical or environmental challenge (c.f. Clark and Peck, 2009a;Clark et al, 2013). Also these represent laboratory-induced experiments and there is an additional requirement to link these through to responses in the natural environment, as the two types of exposure and the associated stress response may not be equivalent (c.f.…”
Section: Candidate Genes For Environmental Ecotoxicologymentioning
confidence: 99%
“…() and Clark et al . () have also performed comprehensive transcriptomic analyses assessing the response of C. virginica and C. gigas , respectively, to a combination of OA and ocean warming. Decreasing pH was shown to increase the immune functions and production of antioxidants in C. gigas , while the combination of both pH and thermal stress induced the expression of protease inhibitors and cytoskeleton‐related genes (Clark et al .…”
Section: Introductionmentioning
confidence: 99%